Investigation of the isothermal section at 1000°C in the Pt-Al-Cr system - Süss R.; Cornish L.A.; Witcomb M.J. (Journal of Mining and Metallurgy. Section B: Metallurgy)
Platinum-based alloys are being developed with γ/γ' microstructures analogous to nickel-based superalloys, with potential for high temperature applications. The ternary Pt-Al-Cr system was investigated to provide data for the continued development of a thermodynamic database for the Pt-Al-Cr-Ru system. The alloys were studied in the 1000°C annealed and quenched conditions, using SEM with EDX and XRD. Isothermal sections were constructed.